The aesthetic proportional anchor of the Calligraphy almathfur kufi (Journal of the College of Basic Education, 2022)
The Kufic line interlaced with its diversity of shapes and the images of its letters still raises many questions and opens wide fields for research and investigation to address the formal and creative structure of its letters, and since these lines have not been thoroughly studied and their rules and scales and their practical dimensions have not been shown, except for what was mentioned theorizing in recognition of their existence by researchers and experts, it was directed The researcher to study this through four chapters, he sought in the first chapter to clarify the problem of research, its importance and the need for it. Through this urgent need for an applied study that stands on the undeclared geometry by the Arab Muslim calligrapher at the time, the researcher sought to clarify it and how the improvements took place later on the line. The plaited Kufi, and its aims to establish an aesthetic proportional engineering base, as well as a set of terms that were assigned to the research from an indicative perspective, to know their merits and operations. As for the second chapter, it included the theoretical framework, in which the research addressed the study of proportionality in the braided kufic line, followed by the proportional balance of the interlaced kufic line in which this balance was achieved and applied to all letters, extracting an alphabet with this type of weighted lines. The researcher came up with a set of indicators . The third chapter was devoted to presenting the research procedures at its outset, then turning afterwards to the application on the plaited kufic line and showing the extent to which the scale applies to them. The research was concluded by presenting the most important results of the research, and through the conclusions the possibility of applying the supposed balance on the plaited kufic line emerged.The fourth chapter was concluded with a number of recommendations emphasizing the importance of the proportional rule for the various lines. The research was concluded with a number of proposals to inspire the proportions of the proportional balance of other early Arabic scripts.